Successful ageing in hybrid work: The role of teleworking quality, engagement, and age on performance - Ramos, S.; Sousa, I.C. (22nd Congress of the European Association of Work and Organizational Psychology (EAWOP), 2025)
Ageing is a prominent trend today, affecting the active workforce and its composition. Simultaneously, the workplace is evolving due to digitalization and the growing adoption of flexible work arrangements, such as teleworking and hybrid models. The continued presence of older workers is inevitable, but under what conditions? Academics and practitioners are exploring how to make work sustainable and ensure successful ageing in the workplace. This study aims to explore which work characteristics can explain the successful performance of workers of different ages, particularly in this transforming world of work. Thus, we examine how the quality of teleworking influences subjective performance. Furthermore, we propose a moderated moderation model where engagement and age moderate this relationship. A sample of 827 employees working in a hybrid model answered an online survey. Findings suggest that the quality of teleworking positively affects subjective performance (B = 1.879, 95% CI = 0.537, 3.221). Finally, there is a three-way effect of the quality of teleworking, engagement and age on performance (B = 0.007, 95% CI = 0.001, 0.015). For low levels of engagement, the effect of the quality of teleworking on performance is higher for younger workers (B = 0.397, 95% CI = 0.227, 0.567) than for older workers (B = 0.236, 95% CI = 0.025, 0.446). On the contrary, for high levels of engagement, the quality of teleworking has a greater effect on the performance of older workers (B = 0.246, 95% CI = 0.084, 0.407) than of younger workers (B = 0.044, 95% CI = -0.138, 0.225). These findings provide valuable insights for the theoretical debate on the concept of successful aging at work, while also highlighting potential pathways for improving job design to enable workers to remain actively employed under conditions that promote both strong performance and well-being.